Controlling aero-elastic instability of curtain wall systems in high-rise buildings - Tan, Ben Hoea; Lucey, Anthony; Pitman, Mark (Modelling and Simulation Society of Australia and New` Zealand Inc, 2011)
Nowadays modern high-rise buildings have unique facades which partly rely on the incorporation of curtain walls. A curtain-wall system encloses the building to separate the internal and external environments. It can reduce building weight and it also transfers the wind load to the floor structure of the building. Wind-load codes govern the design of safe curtain wall systems against natural wind forces, considering direct static and dynamic pressure. In this paper aero-elastic considerations are investigated as a potential failure mode of curtain walls. Curtain-wall panels are regarded as comprising a flexible material such as glass and aluminium cladding subjected to an airflow that is parallel to their surface. It is well-known that a flexible panel exposed to increasingly high flow speed will succumb to a divergence, or static buckling-type, instability at a particular critical flow speed. At a higher flow speed the panel will experience violent oscillatory flutter-type instability. Accordingly, we investigate the susceptibility of curtain-wall panels to aero-elastic effects. A state-space model, based upon computational modelling, is used to investigate the aero-elastic stability of each flexible panel in isolation. We briefly present a recently developed approach and its new extension to theoretical modelling of the fully-coupled interaction between a simply-supported flexible panel and a fluid flow.We solve the boundary-value problem to determine the long-time response and investigate the effects on stability of adding localised structural inhomogeneity. Localised structural inhomogeneity is incorporated as an additional single spring type support to the panel. The dependence of instability onset-flow speeds, and the forms of divergence and flutter instabilities, upon the added spring stiffness and its location are then investigated. Results show that the morphology of the unstable solution space significantly differs from that of the oft-studied corresponding hydro-elasticity problem because of the different density ratio between fluid and solid media. Of particular interest is that in the present aero-elastic system flutter occurs through the coalescence of two non-oscillatory unstable divergence modes. The inclusion of a localised spring support to an otherwise unsupported panel is shown to be stabilising with respect to the critical divergence-onset flow speed and the limits to this strategy are identified. This strategy is marginally destabilising with respect to the more damaging flutter instability that occurs at higher wind speeds. However, at a sufficiently high spring-stiffness a sudden change to the solution morphology occurs that yields two unstable non-oscillatory divergence modes and flutter is postponed to much higher wind speeds.We close the paper with an assessment of what these results mean in dimensional terms as applied to different cladding panels. Overall, our results suggest a means to ameliorate adverse aero-elastic effects in potentially disastrous extreme wind-force situations such as those encountered in typhoons and tropical cyclones.